Pediatric split liver transplantation using a hyperreduced left lateral segment graft in an infant weighing 4 kg - Jung-Man Namgoong; Shin Hwang; Dae-Yeon Kim; Gi-Won Song; Chul-Soo Ahn; Kyung Mo Kim; Seak Hee Oh (Korean Journal of Transplantation, 2020)
We present a case of successful split liver transplantation (LT) using a hyperreduced left lateral segment (LLS) graft in a 106-day-old female infant patient weighing 4 kg. The patient was diagnosed with progressive familial intrahepatic cholestasis. Her general condition and liver function deteriorated progressively and she was finally allocated for a split LT under status 1. The deceased donor was a 20-year-old female weighing 63.7 kg. We performed in situ liver splitting and in situ size reduction sequentially. The weight of the hyperreduced LLS graft was 225 g, with a graft-recipient weight ratio of 5.5%. We performed recipient hepatectomy and graft implantation according to the standard procedures for pediatric living-donor LT. Since the graft was too large for primary abdomen closure, the abdominal wall was closed in three stages to make a prosthetic silo, temporary closure with a xenograft sheet, and final primary repair over 2 weeks. The patient has been doing well for more than 6 years after transplantation. In conclusion, split LT using a hyperreduced LLS graft can be a useful option for treating small infants. However, large-for-size graft-related problems, particularly in terms of graft thickness, still remain to be solved.